1967
DOI: 10.1037/h0024550
|View full text |Cite
|
Sign up to set email alerts
|

Factor analysis of counselor communications.

Abstract: The problem of operationalizing facilitating characteristics of counseling is approached through factor analytical procedures. Each counselor communication in 2 sessions was rated on a warm-cold continuum by students enrolled in guidance courses. Using Vanmax procedure, 10 factors were extracted for the 1st session and 8 factors for the 2nd The factors have been labeled and discussed. It was concluded that the method used is effective for exploring the counseling process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1968
1968
1982
1982

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…A list of practicum supervisor behaviors commonly used in supervision sessions was compiled from earlier research devoted to the supervision process (Patterson, 1964;Worthington & Roehlke, 1979;Zimmer & Park, 1967). It was distributed to faculty and graduate students (n = 20) with practicum supervision experience in the counseling department of a large midwestern university.…”
Section: Methodsmentioning
confidence: 99%
“…A list of practicum supervisor behaviors commonly used in supervision sessions was compiled from earlier research devoted to the supervision process (Patterson, 1964;Worthington & Roehlke, 1979;Zimmer & Park, 1967). It was distributed to faculty and graduate students (n = 20) with practicum supervision experience in the counseling department of a large midwestern university.…”
Section: Methodsmentioning
confidence: 99%
“…The 31 variables by which each response was rated have been operationally defined elsewhere by Mc-Nair and Lorr (1964), Psathas andArp (1966), Wolberg (1954), and Zimmer et al (Zimmer & Andersen, 1968;Zimmer & Park, 1967;Zimmer, Wightman, & McArthur, 1970).…”
Section: Methodsmentioning
confidence: 99%
“…retical orientation and technin"pg of-thA counselor are at best subordinate and perhaps insignificant variables. Zimmer and Park (1967), Zimmer and Anderson (1968), and Zimmer, Wightman, and McArthur (1970) have identified 31 counselor process variables (types of counselor responses). The purpose of this study is two-fold: (a) to attempt to recast 31 variables into a smaller number nf fartqrs which would more parsimoniously describe important dimensions of counselor behavior and (b) to compare the counseling styles of Perls by assigning derived factor scores to random samples of their responses.…”
mentioning
confidence: 99%
“…Swensen (1967) has shown that therapist behavior differences can be usefully measured with an interpersonal interaction circle based upon combinations of active-passive and love-hate dimensions. Whereas factor-analytic procedures have been applied to study the separate and combined dimensions of therapist attitudes (McNair & Lorr, 1964;Sundland & Barker, 1962), the dimensions of ratings of small samples of therapist verbal behavior (Howe, 1962a(Howe, , 1962b(Howe, , 1964Howe & Pope, 1961a;Raush, Sperber, Rigler, Williams, Harway, Bordin, Dittman, & Hays, 1956;Zimmer & Anderson, 1968;Zimmer & Park, 1967), and the dimensions of client perceptions of therapists (Lorr, 1965), factor-analytic procedures remain to be applied to the hypothesized dimensions of overt therapist interactive behavior. Such a study should be based upon correlations among individual scales in a large heterogeneous therapist sample which represents all known sources of variance (e.g., professional grouping, experience level, therapist sex; see McNair & Lorr, 1964, p. 271).…”
Section: Affective Context Of Therapist Activenessmentioning
confidence: 99%